A Geographic Approach for Teaching about Terrorism. Issue 6 (2nd November 2017) - Haney, Jennifer
ABSTRACT: Geography is in a unique position to address the topic of terrorism both inside and outside the classroom and has much to offer in terms of crafting effective measures to counter some of the most pressing threats to international security. As little consideration has been given to teaching about this important subject matter at the university level, this article presents an upper-level special topics case study course offered on terrorism. A capstone project that required students to apply course concepts to a specific terrorist organization is examined and the article concludes with a discussion of the limitations of this pedagogical approach.